2018
DOI: 10.1029/2017jf004280
|View full text |Cite
|
Sign up to set email alerts
|

Critical Zone Structure Under a Granite Ridge Inferred From Drilling and Three‐Dimensional Seismic Refraction Data

Abstract: Observing the critical zone (CZ) below the top few meters of readily excavated soil is challenging yet crucial to understanding Earth surface processes. Near‐surface geophysical methods can overcome this challenge by imaging the CZ in three dimensions (3‐D) over hundreds of meters, thus revealing lateral heterogeneity in subsurface properties across scales relevant to understanding hillslope erosion, weathering, and biogeochemical cycling. We imaged the CZ under a soil‐mantled ridge developed in granitic terra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
158
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(172 citation statements)
references
References 120 publications
(208 reference statements)
11
158
3
Order By: Relevance
“…The burial of valley bottoms with sediment, for example, will tend to tend to reduce cross-valley curvature and locally increase transmissivity. In addition, both numerical simulations and field measurements have shown that the layer of permeable fractured bedrock becomes thinner (smaller a) as topographic curvature increases (Flinchum et al, 2018;Moon et al, 2017). Near drainage divides, valley heads tend to be relatively smooth and un-incised, but farther downstream localized stream incision can narrow valley widths and confine flow laterally (Figure 2c).…”
Section: Downstream Trends Of Valley Transmissivitymentioning
confidence: 97%
“…The burial of valley bottoms with sediment, for example, will tend to tend to reduce cross-valley curvature and locally increase transmissivity. In addition, both numerical simulations and field measurements have shown that the layer of permeable fractured bedrock becomes thinner (smaller a) as topographic curvature increases (Flinchum et al, 2018;Moon et al, 2017). Near drainage divides, valley heads tend to be relatively smooth and un-incised, but farther downstream localized stream incision can narrow valley widths and confine flow laterally (Figure 2c).…”
Section: Downstream Trends Of Valley Transmissivitymentioning
confidence: 97%
“…The range in seismic velocity within this layer (0.5–1.2 km s −1 ) corresponds to varying degrees of weathering. At the soil/saprolite boundary, the saprolite is mainly composed of loose, decomposed granite, whereas the bottom of the layer retains the original rock fabric (Flinchum et al, ). A prominent dipping structure, shown by high resistivity and strong GPR reflections, appears within the saprolite layer on the NE side of the profile (Figure a).…”
Section: Discussionmentioning
confidence: 91%
“…Large corestones are distributed throughout the area and can be seen partially buried close to the location of the anomaly (Figure a). An anomalously high velocity greater than 3.0 km s −1 at this location further supports the fact that this feature is much closer in structure to solid granite bedrock (~4.0 km s −1 ; Flinchum et al, ) than surrounding saprolite. Another region with velocities greater than 3.0 km s −1 can be seen around 40 m. In general, the large velocity gradient supports the interpretation of a subsurface in which fractured and solid bedrock is reached at a shallow depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saprolite is a material that has been significantly chemically altered but still retains the physical structure of the parent material (Lebedeva et al, 2007; Riebe and Granger, 2013; Langston et al, 2015). The fractured rock layer has the highest fracture density near the saprolite boundary and decreases away from this boundary (Wyns et al, 2004; Ayraud et al, 2008; Flinchum et al, 2018b). Unaltered bedrock occurs at a depth where the fracture density is low enough to prevent meteoric water from being circulated, limiting chemical reaction rates.…”
mentioning
confidence: 99%